SUSTAINABLE URBAN PUBLIC PARK LANDSCAPE DESIGN CRITERIA BASED ON COMMUNITY PERCEPTION AND ASPIRATIONS - Ida Bagus Rabindra; Titiek Poerwanti Debora; Ina Krisantia (Journal of Synergy Landscape, 2021)
This article interprets the perception and aspirations of the city community, as a cornerstone of drafting the design criteria of a community-based city park landscape, which is effective and sustainable. Flooding and drought problems in Jakarta and surrounding areas should be resolved in a comprehensive, integrated and sustainable manner. Referring to the Water Sensitive Urban Design (WSUD) which is an innovation in integrated water management, it is recommended to develop the function of detention and retention ponds as part of storm drainage system, replacing conventional system. Development of the city park landscape criteria as the synergies of the RTH function and the detention/retention ponds should be approached in a very careful, avoiding fatal malfunction and harsh rejection of the user community. The best approach should be done through tracing the needs, desires and expectations of the city community as the ‘end user' as well as 'super client' of the city park. Research on the perception and aspirations of the city community on the idea of the development of City Park with the role of retention/retention ponds has been conducted between February to May 2020 in Jabodetabek.